Implementasi Blended Learning sebagai Alternatif dalam Pembelajaran PAI di Era 4.0 - Rafika Zahra (South Sulawesi Education Development, 2024)
The current world condition is starting to enter the industrial era 4.0, which is marked by the development of interaction, connectivity, artificial intelligence, visuals, and the development of digital systems. Increasingly focused on the boundaries of humanity, ICT (Information and Communication Technology) will impact several sectors of life. One of the impacts is that it will affect the education system in Indonesia. In this research the author uses a literature study by finding and collecting relevant data and theories according to the problem cases that have been determined. The literature study method is a literature search method that combines theories from published or unpublished scientific works, which are available in hardcopy and softcopy form, in the form of open books, e-books, and online journals. There are also several other advantages of implementing the blended learning model, namely making it easier for students to access learning materials, increasing the quality of learning, and minimizing costs. Through the accessibility aspect, educators can more easily present learning materials or media online so that students can access them many times and anywhere via an internet connection using smartphones and laptops. Digital learning is essential in the Industrial Era 4.0. Advances in information and communication technology have provided an extraordinary transformation in the world of education, including implementing learning in schools. Universities are carrying out significant transformations with the threat of a pandemic, forcing learning to be done online. Therefore, an online learning system supported by a learning management system (LMS) is essential to implementing learning.